A reappreciation of ‘conformity’ - van Leeuwen, Edwin J.C.; Acerbi, Alberto; Kendal, Rachel L.; Tennie, Claudio; Haun, Daniel B.M. (Animal behaviour, 2016)
•This article presents a follow-up analysis of what constitutes ‘conformity’.•Do we conclude ‘conformity’ when a majority of behaviours, not individuals is copied?•Do we conclude ‘conformity’ when subjects follow one individual instead of a majority?•We present reasons why conflating behaviours and individuals is problematic.•Vital to empirical studies on transmission biases are individual observation records.